Endodontic Treatment of a Large Periradicular Lesion: A Case Report - Asgary, Saeed; Ehsani, Sara (Iranian Endodontic Journal, 2009)
This case report describes the endodontic treatment of a large cyst-like periradicular lesion a 29-year-old female with a large chronic periapical abscess in the region of right maxillary sinus presented into private practice, accompanied with non-vital first upper molar and poorly root treated second upper molar. Conservative root canal treatment was carried out for both of the involved teeth in a single appointment. Post operative examination after two weeks revealed complete resolution of the sinus tract. The clinical and radiographic examination after 9 months revealed complete periapical healing. The appropriate diagnosis of periradicular lesion and the treatment of the infected root canal system allowed complete healing of these large lesions without endodontic surgery.